2022
DOI: 10.3390/medicina58101344
|View full text |Cite
|
Sign up to set email alerts
|

Crohn’s Disease and Jejunal Artery Aneurysms: A Report of the First Case and a Review of the Literature

Abstract: Background and Objectives: Jejunal artery (JA) and ileal artery (IA) aneurysms constitute less than 3% of all visceral artery aneurysms (VAAs), carrying a risk of rupture as high as 30%, and a mortality of 20%. Though many etiologies have been reported in the literature, no mention exists on a causal association between these aneurysms and inflammatory bowel diseases (IBD). We present the first case of a JA aneurysm related to Crohn’s Disease (CD) together with a review of the literature. Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Distal SMA branch vessel aneurysms are exceedingly rare 8. A literature review spanning 80 years identified just 103 cases of jejunal and ileal artery aneurysms,9 the majority of which were due to atherosclerotic, infectious or inflammatory (most often polyarteritis nodosa) aetiologies 9. Ileocolic artery aneurysms account for only 3% of all visceral artery aneurysms 10.…”
Section: Discussionmentioning
confidence: 99%
“…Distal SMA branch vessel aneurysms are exceedingly rare 8. A literature review spanning 80 years identified just 103 cases of jejunal and ileal artery aneurysms,9 the majority of which were due to atherosclerotic, infectious or inflammatory (most often polyarteritis nodosa) aetiologies 9. Ileocolic artery aneurysms account for only 3% of all visceral artery aneurysms 10.…”
Section: Discussionmentioning
confidence: 99%
“…A few case reports have described simple ligation and excision of a jejunal branch as an option if the collateral blood flow is adequate and the bowel seems viable. 11 Only six other mycotic jejunal pseudoaneurysm cases are documented, four involving aneurysmectomy alone, one involving ligation and excision with segmental bowel resection, and one treated conservatively without surgical intervention due to its distal location. 19 , 21 , 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…In cases where the exact bleeding localization can be determined by angio-CT before the minimally invasive procedure, it proves beneficial for subsequent emergency angiography. In critical conditions, emergency angiography can be performed as an overview, followed by selective and superselective imaging to locate the bleeding source, leading to immediate embolization (34,35). With the continuous development of endovascular transcatheter embolization techniques, careful consideration is given to the placement of embolization material, primarily coils, alone or in combination with liquid embolics.…”
Section: Discussionmentioning
confidence: 99%